Familial Mediterranean fever: Health-related quality of life and associated variables in a national cohort - Şebnem ATAMAN,; İlhan SEZER,; Banu SARIFAKIOĞLU,; Kemal NAS,; Mehmet NAYİMOĞLU,; Meltem Alkan MELİKOĞLU,; Sertaç KETENCİ,; Hüseyin Kaplan,; Ali Nail DEMİR,; Gökhan ÇAĞLAYAN,; Ahmet Kıvanç CENGİZ,; Duygu ALTINTAŞ,; et al. (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the effectivity of Familial Mediterranean Fever Quality of Life (FMF-QoL) Scale for the measurement of QoL in patients with FMF and to perform correlations between related clinical variables in Turkish patients. Patients and methods: This multicenter prospective study performed between December 2017 and November 2018 included 974 FMF patients (334 males, 640 females; median age: 35; range, 26 to 45 years). Sociodemographic characteristics and clinical features were recorded. All participants were asked to complete the FMF-QoL Scale, Short Form-36 (SF-36), Hospital Anxiety and Depression Scale (HADS), Health Assessment Questionnaire (HAQ), and Functional Assessment of Chronic Illness Therapy (FACIT) Scale. Results: The median FMF-QoL Scale score was 26. Higher FMF-QoL Scale scores were shown to be related to female sex, illiteracy or primary education, monthly low-income (US$<300), smoking, late-onset FMF (>20 years), a higher number of attacks per month (>1/month), and severe disease. FMF-QoL Scale scores were correlated negatively with subscales of SF-36, and positively with HADS-anxiety and HADS-depression scores, HAQ and FACIT. Conclusion: Female sex, smoking, lower educational status, more severe disease, fatigue, and functional impairment were associated with poor QoL. FMF-QoL Scale was noted as a valid and simple patient-reported outcome instrument and correlated with the SF-36 scale.